FAKTOR PENDORONG PERNIKAHAN USIA REMAJA DI DESA PERHENTIAN SUNGKAI, KECAMATAN PUCUK RANTAU KABUPATEN KUANTAN SINGINGI, RIAU - Efinda, Dona; Firdaus, Firdaus; Yasin, Faishal (Pendidikan Sosiologi, 2013)
Based on data from the Religious Affairs Office (KUA) in the village of Perhentian Sungkai the data obtained in 2012 that 43.75% of the couples who perform marriages still in their teens. Number of couples getting married in the teenage years from 2010 to 2012 has increased. Marriage in their teens has been going on from the previous years. The purpose of this study was to describe the factors driving teen age marriage and describe the welfare conditions of households were married in their teens in the village of Perhentian Sungkai Sub-district Pucuk Rantau Regency Kuantan Singingi Riau. The theory used in this study is the theory of family well-being contained in Law No. 10 of 1992 concerning limitation prosperous family.This study used a qualitative approach whereas this type of research is descriptive. Informants in this study were a married couple and the teen years. Data was collected by observation and direct interviews. The researcher also did a study that documents supporting data and evidence used by the author to support the data collection. Analysis of the data using the model Milles and Huberman.From research conducted in the village of Perhentian Sungkai can be concluded that the motivating factor in the Village wedding teens stop Sungkai is: for reasons of promiscuity, education and their own desires. Economic conditions that couples married in their teens stop Sungkai village is a category Prosperous I and II.